Digitalization in the tourism industry of Kazakhstan - Mussina, K.P.; Mamrayeva, D.G.; Lemanowicz, M. (BUKETOV BUSINESS REVIEW, 2020)
Object: The article substantiates the need to use Internet technologies for the development of the tourism industry of Kazakhstan at the present stage, since tourism industry is characterized by a variety of intermediary schemes, so the need for using Internet technologies is increasing here. In particular, the authors pursue a goal to research the specifics of digitalization in the field of tourism and current problems limiting contribution of digitalization to increasing the competitiveness of the industry. Methods: Such general scientific methods as statistical analysis, content analysis were employed for conducting the current research. Findings: The article describes key areas of digital transformation of the tourism industry in the era of the digital economy, and also shows the advantages of digital transformation for the tourism industry, which are to deepen the knowledge of the tourists based on the provision of detailed information about places of recreation and travel; reduction of time for entry and exit of information, management and administrative processes. Conclusions: This paper analyzes the current state of the tourism sector in Kazakhstan, presents the results of conducted analysis on ICT readiness in the context of Kazakhstani tourism industry. The perspective impact of digitalization on this industry is also considered.